Front yard robbery action detection: climb-over-gate action analysis - Lim, Kar Heng (2021)
Many families will install motion-detection sensors for security and surveillance systems. However, these systems have their own limitation. The alarm can be triggered by any moving objects such as a passing animal. A guard is required to constantly checking on the screen of what being recorded to know if a robbery is occurring for a normal surveillance system. In this paper, a surveillance system using computer vision and pattern recognition is proposed. The system will begin monitoring the front yard after it has been activated by the user. During the monitoring processes, the system will keep track of the action begin done and an alarm will be triggered when a climbing/jumping over gate or fence action is detected.